2012
DOI: 10.1021/nl301702r
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Single Layered WSe2 p-FETs with Chemically Doped Contacts

Abstract: We report high performance p-type field-effect transistors based on single layered (thickness, ∼0.7 nm) WSe(2) as the active channel with chemically doped source/drain contacts and high-κ gate dielectrics. The top-gated monolayer transistors exhibit a high effective hole mobility of ∼250 cm(2)/(V s), perfect subthreshold swing of ∼60 mV/dec, and I(ON)/I(OFF) of >10(6) at room temperature. Special attention is given to lowering the contact resistance for hole injection by using high work function Pd contacts al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

72
1,502
4
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,656 publications
(1,611 citation statements)
references
References 24 publications
72
1,502
4
3
Order By: Relevance
“…1,4 However, the number of studies on TMDs other than MoS 2 is still small. 5−14 Among these studies, back-gated WSe 2 monolayer FETs with surface doping have already demonstrated a high field-effect mobility 8 reaching ∼140 cm 2 V −1 s −1 , which is substantially higher than most of the reported roomtemperature mobility values for MoS 2 . 15−19 A high intrinsic hole mobility of up to 500 cm 2 V −1 s −1 was also observed in bulk WSe 2 FETs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,4 However, the number of studies on TMDs other than MoS 2 is still small. 5−14 Among these studies, back-gated WSe 2 monolayer FETs with surface doping have already demonstrated a high field-effect mobility 8 reaching ∼140 cm 2 V −1 s −1 , which is substantially higher than most of the reported roomtemperature mobility values for MoS 2 . 15−19 A high intrinsic hole mobility of up to 500 cm 2 V −1 s −1 was also observed in bulk WSe 2 FETs.…”
mentioning
confidence: 99%
“…Low-resistance contacts have been achieved by surface doping of WSe 2 (e.g., with NO 2 and K) in order to reduce the SB thickness, or by using low work function contact metals such as indium in order to lower the height of the SB to the conduction band. 8,10,12 However, …”
mentioning
confidence: 99%
“…6,7 The performance of current metal-contacted TMDs is limited by the presence of a significant Schottky barrier (SB) in most cases. [8][9][10][11]12 In silicon-based electronics, low-resistance ohmic contacts are achieved by selective ion implantation of drain/source regions below metal electrodes. In this way, the contact barrier width between the metal electrodes and degenerately doped source and drain regions is significantly reduced.…”
mentioning
confidence: 99%
“…Furthermore, the 1T phase MoS 2 is thermally unstable above 100 o C. The availability of a variety of semiconducting TMDs such as MoSe 2 , WS 2 and WSe 2 with different band structures and charge neutrality levels offers additional distinct properties and opportunities for device applications. 5,6,8,9,13,[26][27][28][29][30][31][32][33][34][35][36][37] However, the variation of electron affinity, band gap, and band alignments also presents significant challenges to contact engineering. To unlock the full potential of TMDs as channel materials for high-performance thin-film transistors, highly effective and versatile contact strategies for making low-resistance ohmic contacts are needed.…”
mentioning
confidence: 99%
“…As one of the most significant members of 2D materials family, transition metal dichalcogenides (TMDs), such as MoS 2 , MoSe 2 , WS 2 , and WSe 2 , have attracted tremendous attention currently due to their outstanding electronic, optical, and mechanical properties 11, 12, 13, 14, 15, 16, 17, 18, 19. Monolayer MoSe 2 is a sandwich structure consisting of one Mo atom and two Se atoms, and the different layers are interacted by van der Waals force 20, 21.…”
mentioning
confidence: 99%